2015
DOI: 10.1016/j.bjid.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and incidence of HIV-1 in a counseling and testing center in the city of Itajaí, Brazil

Abstract: Itajaí is a port city in southern Brazil with one of the highest incidence and mortality rates from AIDS in the country. The prevalence and incidence of HIV infection were investigated in 1085 of 3196 new HIV-1 infection cases evaluated in the counseling and testing center of Itajaí from January 2002 to August 2008. Recent infections were assessed using the BED™, and pol region sequencing was performed in 76 samples. The prevalence ranged from 3.08% to 6.17% among women and from 10.26% to 17.36% among men. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
6
0
5
Order By: Relevance
“…In Jatai, the male/female ratio was 0.9:1 in 2008 and 1.4:1 during the study period 15 . In contrast to the national trend, the incidence of HIV infection among women is increasing in some cities of the interior of Brazil 4 , 10 , 16 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In Jatai, the male/female ratio was 0.9:1 in 2008 and 1.4:1 during the study period 15 . In contrast to the national trend, the incidence of HIV infection among women is increasing in some cities of the interior of Brazil 4 , 10 , 16 .…”
Section: Discussionmentioning
confidence: 80%
“…In this region, Goias State holds the highest number of cases of HIV infection: 1,004 cases were recorded in 2015, with an incidence rate of 15.2 cases/100,000 inhabitants. Although prevalent in heterosexual males, HIV infection among men who have sex with men (MSM) and heterosexual females is increasing 2 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…This method has the limitation of increasing uncertainty in more recent years, as newly reported cases provide information only on past incidence. Incidence assays can identify recently acquired infections and could be incorporated to improve estimations, but as yet, have been trialled in only a few small studies in limited regions in Brazil (Szwarcwald et al, 2016b; de Castro et al, 2010; Grinberg et al, 2015). Information on the CD4 progression rates and mortality without ART are not available for Brazil and we therefore acquired data from other sources, conducting an uncertainty analysis to assess the robustness of our results under a range of assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the rates of TDR in HIV-1-infected adults have varied between 4 and 16% using Sanger sequencing of HIV RNA population from plasma [1422] except for Amapá State, with a rate of 1% [23], similar to the lower rates (2%) found in the country in early 2000s [24]. Some studies have suggested a small, non-significant increase in the frequency of TDRM among HIV-1-infected adults in the last years, mainly to the NNRTI class, followed by NRTI and PI [14, 15], being the TDRM rates of 23% in HIV patients in the acute phase and 13–18% in patients with recent chronic infection [12, 14, 18, 25]. The clinical consequences of the presence of TDRM include a longer time to reach virological suppression and a higher risk of treatment failure [26, 27].…”
Section: Transmitted Hiv Drug Resistance In Brazilmentioning
confidence: 99%